Phenomenological Analysis of The Rising Online Gambling Among Students in Kediri - Arrafif, Arafat Irhabi; Wiguna, Frans Aditia (Universitas Negeri Malang, 2023)
This study analyzes the rise of online gambling among department primary teacher education students at Universitas Nusantara PGRI Kediri. The method used in this research is descriptive qualitative. The data collection technique used is observation or observation and in-depth interviews. The informants in this study were as many as 32 students. Online gambling is popular among students: slot gambling and soccer betting. Then players who play online gambling have several factors that make them play, namely: 1) Lack of understanding of religion, 2) Social factors, 3) Economic factors, 4) Lack of education factor, and 5) The influence of technology. In addition, researchers also found negative impacts from online gambling, namely: 1) Addiction, 2) Mental disorders, 3) Decreased economic level, and 4) Lots of debt. In this study, there are also efforts to prevent someone from online gambling, namely: 1) Looking for busyness, 2) Looking for a new environment, 3) Working well with finances, 4) Socialization, 5) Studying religion, 6) Wise in using the internet. Analisis Fenomenologis Maraknya Judi Online di Kalangan Mahasiswa di Kediri Penelitian ini bertujuan untuk menganalisis maraknya judi online dikalangan mahasiswa Pendidikan Guru Sekolah Dasar Universitas Nusantara PGRI Kediri. Metode yang digunakan pada penelitian ini adalah kualitatif deskriptif. Teknik pengumpulan data yang digunakan adalah observasi atau pengamatan dan wawancara mendalam. Informan dalam penelitian ini sebayak 32 mahasiswa. Ada dua bentuk judi online yang marak dikalangan mahasiswa yaitu judi slot dan judi bola. Lalu pemain yang bermain judi online memiliki beberapa faktor yang membuat mereka bermain yaitu: 1) Faktor kurangnya pemahaman agama, 2) Faktor pergaulan, 3) Faktor ekonomi, 4) Faktor kurangnya Pendidikan, 5) Pengaruh teknologi. Selain itu peneliti juga menemukan dampak negatif dari judi online yaitu : 1) Kecanduan, 2) Gangguan mental, 3) Penurunan taraf ekonomi, 4) Banyak berhutang. Pada penelitian ini juga terdapat upaya agar seseorang terhindar dari judi online yaitu : 1) Mencari kesibukan, 2) Mencari lingkungan baru, 3) Mengatur keuangan dengan baik, 4) Sosialisasi, 5) Belajar agama, 6) Bijaksana dalam menggunakan internet.